Assessing the quality of bereavement care after perinatal death: development and piloting of a questionnaire to assess parents' experiences. (3rd October 2017) - Aiyelaagbe, Esther; Scott, Rebecca E.; Holmes, Victoria; Lane, Emma; Heazell, Alexander E. P.
Abstract: Understanding parents' experience of care is essential to develop high-quality perinatal bereavement services. This study aimed at developing a questionnaire to identify parents' needs and record their experience of care. The patient experience questionnaire was developed by professionals and parents, and piloted in a tertiary maternity unit. Responses were received from 58 parents. Sensitivity and kindness of staff and time spent with their baby were ranked as 'very important' by 95% of parents. Care in these areas largely met their needs (90%), although 5% of respondents stated that partners could have been more involved. Between 8% and 15% of respondents did not feel that language used at the diagnosis of fetal death was sensitive, clear and unambiguous. Parents did not always receive written information about their care (5%) or post-mortem (13%). Analysis of bereaved parents' responses identified areas for improvement including greater involvement of partners and a need for timely information. Impact statement: What is already known on this subject?: Good quality bereavement care after perinatal death reduces the negative emotional, psychological and social effects for parents. Description of parents' experiences is a potential means to improve the quality of perinatal bereavement care. What do the results of this study add?: Parents' needs and experiences of care after perinatal death were recorded using a patient-experience questionnaire designed by a multi-professional team and parents. Staff behaviour, particularly sensitivity and kindness was highly valued by parents. Giving both verbal and written information could be improved. Training is needed for professionals, particularly those who come into contact with bereaved parents less frequently. What are the implications of these findings for clinical practice and/or further research?: Description of parents' priorities and views can be used to identify areas for improvement in perinatal bereavement care. Parents' views should be regularly sought and used to develop local services in an iterative process.